KESANTUNAN BERBAHASA DALAM FILM “SEJUTA SAYANG UNTUKNYA” KARYA HERWIN NOVIANT: KAJIAN PRAGMATIK (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
This study aims to determine how the representation of the characters' speech in the film "Sejuta Sayang Untuknya" directed by Herwin Noviant, especially in the aspect of language politeness. This research method uses qualitative methods with a pragmatic approach. The source of research data is the film “Sejuta Sayang Untuknya”, directed by Herwin Noviant. The data technique used was listen and note. The data studied is based on maxims which are generally followed to show politeness towards the interlocutor. The maxims used are the maxim of generosity, the maxim of appreciation, the maxim of simplicity, the maxim of consensus, and the maxim of sympathy.